Directions of state support for innovative activities in the sphere of regional services - Fayzieva Shirin Shodmonovna (THE INNOVATION ECONOMY, 2026)
The article examines the mechanisms for the widespread implementation of innovative activities, providing business entities with modern infrastructure and financial resources, providing systemic support from the state, and substantiates the directions for improving the service sector for the future.